Biopsychronology: live confocal imaging of biopsies to assess organ function. (17th June 2014) - Ashraf, Muhammad Imtiaz; Fries, Dietmar; Streif, Werner; Aigner, Felix; Hengster, Paul; Troppmair, Jakob; Hermann, Martin
Summary Prolonged ischemia (I) times caused by organ procurement and transport are main contributors to a decrease in organ function, which is further enhanced during reperfusion (R). This combined damage, referred to as ischemia–reperfusion injury (IRI), is a main contributor to delayed graft function, which leads to costly and lengthy follow‐up treatments or even organ loss. Methods to monitor the status of a graft prior to transplantation are therefore highly desirable to optimize the clinical outcome. Here, we propose the use of fine needle biopsies, which are analyzed by real‐time live confocal microscopy. Such a combination provides information about the functional and structural integrity of an organ within a few minutes. To confirm the feasibility of this approach, we obtained fine needle biopsies from rodent kidneys and exposed them to various stress conditions. Following the addition of a range of live stains, biopsies were monitored for mitochondrial function, cell viability, and tissue integrity using confocal live cell imaging. Our data demonstrate that this procedure requires minimal time for sample preparation and data acquisition and is well suitable to record organ damage resulting from unphysiological stress.